The effect of decrease in serum nitric oxide concentration on portal hemodynamics after Helicobacter pylori treatment: An open-label pilot study - Ender SERİN; M. Ali POURBAGHER; Yüksel GÜMÜRDÜLÜ; Lülüfer TAMER; Birol ÖZER; Uğur YILMAZ (Turkish Journal of Gastroenterology, 2019)
-